Differences between the creativity of people who are deaf or hard of hearing and those with typical hearing: a protocol for the further scoping review - Potměšilová, Petra; Potměšil, Miloň; Klugar, Miloslav (Creativity Studies, 2024)
As a step prescribed by the Joanna Briggs Institute methodology before conducting a scoping review, the protocol aims to describe differences in creativity between deaf and hard of hearing and typically hearing people. Creativity as a mental process is important for the development of personality, imagination, communication skills, and interpersonal relationships. For this study, the focus was on creativity of deaf and hard of hearing persons. Deaf and hard of hearing people show specific characteristics in their mode of creativity. All the studies that deal with creativity in deaf and hard of hearing people will be included. Studies of any design in English, German, or Czech will be accepted as sources for assessment and analysis for systematic review. The Joanna Briggs Institute methodology for a scoping review will act as a framework for the review that will be prepared. 14 scientific databases will be chosen for this review. Two independent reviewers will identify and evaluate all the titles and abstracts that are acquired. The selected data will be extracted and reported in tabular form and a descriptive format.